El proceso didáctico y los problemas de aprendizaje de lectoescritura de los estudiantes de 4to año de educación general básica - Perero Holguín, Elizabeth Hermelinda (2021)
The thesis to obtain the title of Master in Education is titled “The didactic process and the problems of learning of literacy of the students of 4th year of elementary basic general education and arises from the interest in literacy as an area of essential human knowledge to achieve knowledge, skills and behaviors throughout life. The problem starts from the need to improve communication in Basic Elementary Education as a support for the educational system. The scientific problem: How does the didactic process affect the learning of literacy in students in the 4th year of basic general education: Determine the incidence of literacy in the development of communication skills of students. The context of the investigation is the "Juan Javier Espinoza" Fiscal Education Unit located in the Tarqui parish, an urban area of the city of Guayaquil, where students study from one level to the next with deficiencies in basic subjects, especially in Language and Literature……………